Product analysis analysis at Yuyun Cell Mobile shop with the monte carlo method - Putri Novrianti Iswanto; Ardy Januantoro (Institute of Computer Science (IOCS), 2023)
In the development of today's business world, business is growing rapidly everywhere and of course the competition is also getting tougher. yuyun cell shop is one of the businesses that often has problems with cellphone product stock, with this the authors conducted research to help predict product stock and reduce dead stock in it. In this case the research method used is waterfall because the approach used for research is systematic and for the analytical method used is the monte carlo method to predict product stock sales because it has algorithms to simulate various systems and their mathematics. The Monte Carlo method is used to determine the prediction of cellphone product stock later to help Yuyun's cellphone shop in optimizing and maximizing cellphone sales. The results of this study are to determine the accuracy of future cellphone stock predictions, with predictions for three categories based on the price range of mobile phone products, namely high end getting an accuracy of 99%, then for the medium category getting a simulation accuracy of 98.14%, and finally low category gets prediction accuracy. 98.16% accuracy.